Associations Between Mild Cognitive Impairment and Hospitalization and Readmission. Issue 9 (27th August 2015) - Callahan, Kathryn E.; Lovato, James F.; Miller, Michael E.; Easterling, Doug; Snitz, Beth; Williamson, Jeff D.
<x xml:space="preserve">Abstract</x> Objectives To determine whether older adults with mild cognitive impairment (MCI), a condition not previously explored as a risk factor, have more hospitalizations and 30‐day readmissions than those with normal cognition. Design Post hoc analysis of prospectively gathered data on incident hospitalization and readmission from the Ginkgo Evaluation of Memory Study (GEMS), a randomized, double‐blind, placebo‐controlled trial designed to assess the effect of Ginkgo biloba on incidence of dementia. Setting GEMS was conducted in five academic medical centers in the United States. Participants Community‐dwelling adults aged 75 and older with normal cognition (n = 2, 314) or MCI (n = 428) at baseline cognitive testing (N = 2, 742). Measurements Index hospitalization and 30‐day hospital readmission, adjusted for age, sex, race, education, clinic site, trial assignment status, comorbidities, number of prescription medications, and living with an identified proxy. Results MCI was associated with a 17% greater risk of index hospitalization than normal cognition (adjusted hazard ratio (aHR) = 1.17, 95% confidence interval (CI) = 1.02–1.34)). In participants who lived with a proxy, MCI was associated with a 39% greater risk of index hospitalization (aHR = 1.39, 95% CI = 1.17–1.66). Baseline MCI was not associated with greater odds of 30‐day hospital readmission (adjusted odds ratio = 0.90, 95% CI = 0.60–1.36). Conclusion MCI may represent a target condition for healthcare providers to coordinate support services in an effort to reduce hospitalization and subsequent disability.